2014
DOI: 10.1002/2014jd021567
|View full text |Cite
|
Sign up to set email alerts
|

Ice nucleation of bare and sulfuric acid‐coated mineral dust particles and implication for cloud properties

Abstract: Ice nucleation properties of atmospherically relevant dust minerals coated with soluble materialsare not yet well understood. We determined ice nucleation ability of bare and sulfuric acid-coated mineral dust particles as a function of temperature (À25 to À35°C) and relative humidity with respect to water (RH w ; 75 to 110%) for five different mineral dust types: (1) Arizona test dust, (2) illite, (3) montmorillonite, (4) K-feldspar, and (5) quartz. The particles were dry dispersed and size selected at 200 nm,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
109
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(114 citation statements)
references
References 89 publications
5
109
0
Order By: Relevance
“…4b), but at 243 K a higher RH w is needed to reach AF = 10 −3 . Kulkarni et al (2014) also reported a reduction in the ice nucleation ability of 200 nm particles of a K-feldspar sample after coating with sulfuric acid. A general reduction in the ice nucleation ability agrees with the immersion freezing measurements on microcline after treatment with nitric acid presented in this work, but sulfuric acid treatment was not tested with PINC.…”
Section: Results Of Deposition and Condensation Mode Measurementsmentioning
confidence: 87%
“…4b), but at 243 K a higher RH w is needed to reach AF = 10 −3 . Kulkarni et al (2014) also reported a reduction in the ice nucleation ability of 200 nm particles of a K-feldspar sample after coating with sulfuric acid. A general reduction in the ice nucleation ability agrees with the immersion freezing measurements on microcline after treatment with nitric acid presented in this work, but sulfuric acid treatment was not tested with PINC.…”
Section: Results Of Deposition and Condensation Mode Measurementsmentioning
confidence: 87%
“…However, the situation is even more complex in the ambient atmosphere, where particles are often present as complex mixtures of different compounds and minerals. Although recent laboratory experiments have considered the influence of aerosol mixing states (Sullivan et al, 2010;Kulkarni et al, 2014;Augustin-Bauditz et al, 2016), the complexity of the atmosphere has not yet been fully represented.…”
Section: Introductionmentioning
confidence: 99%
“…The internal mixing of particles is an important factor that contributes to the complexity of atmospheric aerosol particles. Although efforts have been made to address the effects of internal mixing on the IN activity of aerosols under conditions relevant for the mixed-phase cloud formation (Sullivan et al, 2010;Kulkarni et al, 2014;Augustin-Bauditz et al, 2016), the complexity of the ambient aerosol has not yet been fully represented by the laboratory-generated aerosols. Therefore, detailed investigation based on the individual particle analysis is necessary to relate the internal mixing state of aerosols in the actual atmosphere and their IN activity.…”
Section: Introductionmentioning
confidence: 99%
“…Deposition and immersion nucleation experiments showed reduced IN efficiency for sulfuric acid-coated feldspar particles (Kulkarni et al, 2014). Zolles et al (2015) reported a decreased IN efficiency for enzyme-treated K-feldspar but after heating the efficiency was restored to the original value.…”
Section: Reversibility Of Surface Modifications 360mentioning
confidence: 99%
“…In this case, active sites might remain intact but disabled to act as INP because of the organic cover. In the absence of surface chemical reactions, the chemical coating might dissolve during cloud droplet activation releasing the mineral surface again restoring the 105 ice-nucleating ability (Sullivan et al, 2010b;Tobo et al, 2012;Kulkarni et al, 2014;Wex et al, 2014).…”
Section: ∆ ∆ mentioning
confidence: 99%